The effect of fatigue on lower limb motor variability during a controlled repetitive stretch-shorten cycle task - Mudie, K. L.; Gupta, A.; Clothier, P. J. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
This study evaluated changes in lower limb joint coupling variability during single-leg hopping to exhaustion. Twenty recreationally active male and female participants performed single-leg hopping at 2.2 Hz to a target height. At 0, 20, 40, 60, 80 and 100% of the total duration of hopping, spatio-temporal characteristics and variability of the kneeankle (KA) and hip-knee (HK) joint couplings were determined. There was a significant increase in variability of the KA and HK joint couplings in the flexion-extension axes during the loading and propulsion phases as hopping progressed. However, there was maintenance of performance output characteristics throughout the task. These findings suggest that changes in joint coupling variability may be a compensatory strategy to allow continuous single-leg hopping as the effects of muscular fatigue increase.